POTENSI DAN STRATEGI PENGEMBANGAN OBYEK WISATA ALAM TAHURA SULAWESI TENGAH DESA NFATABARU KABUPATEN SIGI - Masriandi, Masriandi; Mallombasang, Sri Ningsih (Jurnal Warta Rimba, 2020)
One of the tourism objects in Sigi Regency, Central Sulawesi Province is the Nature Park of the Great Forest Park (TAHURA) in Ngatabaru Village, Sigi Regency, Central Sulawesi Province. This tourism object is managed by the Ministry of Forestry of Central Sulawesi Province. The purpose of this study was to determine the potential and determine the TAHURA Natural Tourism Object Development Strategy in Central Sulawesi, Ngatabaru Village, Sigi Regency. the usefulness of this research is to provide information and intake for the Development of TAHURA Nature Tourism Object in Central Sulawesi, Ngatabaru Village, Sigi Regency. The method used in this research is descriptive qualitative method. Data collection techniques are observation, interview and also documentation taking. The analysis used in this research is SWOT Analysis. TAHURA Natural Tourism Object Area of Central Sulawesi has the potential of natural resources such as flora and fauna, natural phenomena and beautiful panorama which is very suitable as a vacation spot for friends and family, as well as the availability of facilities and infrastructure to support the natural tourism area. Strategies that must be carried out for the development of natural tourism are attracting tourists in and outside the area to visit these attractions with the wealth of existing natural resources by tightening the security of tourist areas, maintenance of facilities and infrastructure and inviting the public to participate in participating in the management of tourist areas alam TAHURA Central Sulawesi.Keywords: Potential, Strategy, Tourism, TAHURA, Central Sulawesi